DIGITAL PULPIT DYNAMICS: UNRAVELING STRATEGIES AND OVERCOMING CHALLENGES IN ISLAMIC DAKWAH IN THE DIGITAL ERA - Siti Nazla Raihana; Annisa Fristyarini; Hani Aufaa Khairunnisa (ORASI: Jurnal Dakwah dan Komunikasi, 2023)
The rapid advancement of technology has significantly impacted various aspects of life, yielding both positive and negative effects. One prominent positive impact is the increased accessibility of information for all individuals. This phenomenon presents a valuable opportunity for Islamic preachers (dai) to disseminate religious messages and reinforce ethical values, known as amar maruf nahi munkar. This research explores the challenges and strategies faced by preachers in the evolving digital era. Using a qualitative approach and interviews with dai from diverse regions in Indonesia, this study identifies key challenges encountered by preachers in the digital realm. These challenges include a lack of expertise in graphic design, the need to filter vast amounts of content and videos, time constraints, fluctuating levels of commitment, and issues related to network connectivity. However, the study also reveals various strategies employed by preachers to address these challenges. These strategies encompass aspects such as praying, assembling competent teams for content management, selecting the right time and place for message delivery, and resolving network-related issues. This research offers critical insights into the dynamics of digital preaching, emphasizing the importance of adaptation and innovation in tackling the challenges faced by Islamic preachers. In conclusion, while technology serves as a potent means of spreading religious messages, a deep understanding of effective strategies is essential to overcome the emerging obstacles.